Bonding Experiments at Elevated Temperatures: The Effect of the Sample Storage Time on the Bond Strength of Metals. Issue 1 (17th October 2022) - Nietsch, Juergen A.; Gouverneur, Moritz; Schwab, Christian; Bailly, David; Martin, Manfred; Hirt, Gerhard
Abstract : Bond formation plays a major role in the production of metallic composites, e.g., in roll bonding, composite ring rolling, and the permanent closure of voids by metal forming at elevated temperatures. At the same time, the determination of the corresponding bonding strength is quite challenging due to various influencing factors. These factors include the impact of the surface roughness and the degree of oxidation. The transition, or rather the storage time between the surface pretreatments and testing, leads to deviations in the surface conditions between the experiment and the industrial process. To evaluate the effect of the sample storage time on the bond strength of aluminum and steel, bonding experiments are conducted with storage times ranging from several minutes to 9 weeks at room temperature. The results show a major reduction of the bond strength between different aluminum alloys with increasing storage time, while the steel bond strength is less affected. The reasons for this are differences in the oxidation behavior of aluminum, tempered steel, and stainless steel. Nevertheless, the results indicate the importance of the storage time at room temperature and bonding parameters at elevated temperatures on the bond strength between these metals. Abstract : For the production of metallic composites, the achievable bonding strength plays a major role in this process. The determination of the bonding strength is quite challenging. One reason for this is the oxidation behavior. Therefore, the effect of storage time on the determination of several metallic bonds is investigated for different bonding conditions.